2016
DOI: 10.1002/2015wr018294
|View full text |Cite
|
Sign up to set email alerts
|

From conservative to reactive transport under diffusion‐controlled conditions

Abstract: International audienceWe assess the possibility to use conservative transport information, such as that contained in transit time distributions, breakthrough curves and tracer tests, to predict non-linear fluid-rock interactions in fracture/matrix or mobile/immobile conditions. Reference simulated data are given by conservative and reactive transport simulations in several diffusive porosity structures differing by their topological organization. Reactions includes non-linear kinetica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…In addition, the presence of damaged zones in the vicinity of fractures can enhance this contrast as they are more transmissive than the matrix (Laurent et al, 2019;Neretnieks, 1980;Wogelius et al, 2020). Such zones may be considered by sub-gridding the rock matrix, as done in the Structured INteracting Continua approach proposed by Babey et al (2016). Hereafter, rather than introducing a third subdomain in our multi-continua model, we merged the damaged zone area with the fracture region and used a D.P.…”
Section: Dual Porosity Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the presence of damaged zones in the vicinity of fractures can enhance this contrast as they are more transmissive than the matrix (Laurent et al, 2019;Neretnieks, 1980;Wogelius et al, 2020). Such zones may be considered by sub-gridding the rock matrix, as done in the Structured INteracting Continua approach proposed by Babey et al (2016). Hereafter, rather than introducing a third subdomain in our multi-continua model, we merged the damaged zone area with the fracture region and used a D.P.…”
Section: Dual Porosity Modelmentioning
confidence: 99%
“…Such zones may be considered by sub‐gridding the rock matrix, as done in the Structured INteracting Continua approach proposed by Babey et al. (2016). Hereafter, rather than introducing a third subdomain in our multi‐continua model, we merged the damaged zone area with the fracture region and used a D.P.…”
Section: Modeling Strategymentioning
confidence: 99%
“…Among them, the mobile-immobile Multi-Rate Mass Transfer models (MRMT) [Carrera et al, 1998;Haggerty and Gorelick, 1995] does not only propose efficient characterization and upscaling methodologies [Willmann et al, 2008;Babey et al, 2015;Rapaport et al, 2017] but also a natural bridge to equivalent concentration distributions, which relevance can be assessed to model reactive transport [Donado et al, 2009;Henri and Fernandez-Garcia, 2015;Sanchez-Vila et al, 2010;Soler-Sagarra et al, 2016]. Synthetic experiments have shown that MRMT models provide close approximations of bulk reactivity even in non-linear equilibrium and kinetically-controlled cases [Babey et al, 2016]. This has been linked to the empirical observation that MRMT models do not only conserve mass by construction but also the porosity weighted integral of concentrations squared [de Dreuzy et al, 2013], which is directly linked to mixing-induced reactivity through the scalar dissipation rate [Le Borgne et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…By reducing concentration variances, diffusive processes induced by mobile-immobile mass exchanges thus promote reactivity and, by consequence, reduce further mixing and reaction potentials.The scalar dissipation rate only differs from the reaction rate by a chemical term that derives from the nonlinearity of the reactivity in the reactant concentrations[De Simoni et al, 2005]. Numerical simulations have however shown that the influence of this chemical term remains limited for most immobile porosity structures and reaction types also extending to heterogeneous reactivity including sorption and precipitation/dissolution[Babey et al, 2016]. The relevance of MRMT to model reactive transport fundamentally comes from the representativity for the concentrationA C C E P T E D M A N U S C R I P TRelevance of MRMT models to reactive transport distribution of its mean and variance in diffusively-dominated conditions.…”
mentioning
confidence: 99%